2014
DOI: 10.1111/ecc.12189
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilisation in patients with breast cancer or non-Hodgkin lymphoma who experienced febrile neutropenia in the Netherlands: a retrospective matched control study using the PHARMO database

Abstract: Few data have been published on healthcare resource utilisation associated with chemotherapy-induced febrile neutropenia (FN) in Europe. Using the PHARMO record linkage system, we identified incident adult patients with a primary hospital discharge diagnosis of breast cancer (BC) or non-Hodgkin lymphoma (NHL) from 1998 to 2008. Patients who experienced FN were matched 1:2 non-FN reference patients. Of 1033 BC patients, 80 (8%) had FN and were matched with 160 reference patients; and of 486 NHL patients, 95 (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…A recent case-control study showed that FN is associated with higher health care resource use in BC patients compared to non-FN patients [45]. BC patients with a history of FN had an increased risk of all-cause hospitalization in the first month after the febrile event compared with patients who never experienced FN (odds ratio (OR) = 23.0, 95% confidence interval (CI) 8.3-63.7) and they also had a longer median length of stay of all-cause hospitalizations (4 days vs. 1 day).…”
Section: Discussionmentioning
confidence: 99%
“…A recent case-control study showed that FN is associated with higher health care resource use in BC patients compared to non-FN patients [45]. BC patients with a history of FN had an increased risk of all-cause hospitalization in the first month after the febrile event compared with patients who never experienced FN (odds ratio (OR) = 23.0, 95% confidence interval (CI) 8.3-63.7) and they also had a longer median length of stay of all-cause hospitalizations (4 days vs. 1 day).…”
Section: Discussionmentioning
confidence: 99%
“…Studies recruiting an EU population accounted for the greatest proportion of research (41%) ( Figure 2D). (16 studies [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39])…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A patient's first FN episode was most likely to occur during the first cycle of chemotherapy [25,27,35]. In both the US and EU/Canada, FN events were predominantly treated in the inpatient setting [31,39]. In the US, up to 84% of patients require at least one hospitalization [30] and many require multiple hospitalizations [25].…”
Section: Summary Findings: Febrile Neutropeniamentioning
confidence: 99%
See 2 more Smart Citations